Size optimization of an off-grid hybrid system composed of photovoltaic and diesel generator subject to load variation factor - Gharibi, Mahdi; Askarzadeh, Alireza (Journal of energy storage, 2019)
•Off-grid PV/diesel hybrid system is optimally sized subject to demand response.•Load variation factor is defined as a decision variable of sizing problem.•Interruptible/curtailable program is used to model DR in sizing problem.•MOPSO and MOCSA are applied to solve sizing problem in a multi-objective framework. This paper focuses on size optimization of a hybrid system composed of photovoltaic (PV) and diesel generator with respect to demand response (DR) program. For this goal, a new index named load variation factor (LVF) is defined and considered as a decision variable of the sizing problem. LVF determines how much load should be decreased in peak hours to optimally minimize the system cost from the system operator's point of view. Size optimization is formulated in multi-objective framework by two important objectives: total net present cost (TNPC) and loss of power supply probability (LPSP). Interruptible/curtailable (I/C) program is used to model DR in the sizing problem. Multi-objective variants of particle swarm optimization (MOPSO) and crow search algorithm (MOCSA) are applied to the problem and the results are compared. Simulation results indicate that optimal determination of LVF can considerably reduce system cost.